Exposure to Lead Compounds in an Industrial Setting and the Effects on the Thyroid Gland: A Pilot Cohort Study - Lidia Caporossi; Simona Di Renzi; Mariangela De Rosa; Silvia Capanna; Elisa Partenzi; Iacopo D’Alessandro; Bruno Papaleo (Hygiene)
Background: Lead compounds are chemicals of high toxicological concern and are suspected to interact with the thyroid axis. Method: A cohort study was carried out involving 70 workers from a petrochemical company exposed to inorganic lead compounds. All recruited workers were given a clinical anamnestic questionnaire aimed at characterizing their endocrine and thyroid status. A blood test was conducted to dose the amount of lead, thyroid hormones (FT3, FT4, TSH), and antibodies (TGAb and TPOAb). Samples were stratified according to working seniority and lead exposure levels. A regression study was conducted to highlight trends in hormones and antibodies versus lead levels. Results: Most of the dosages are within the normal ranges. The regression study showed how higher lead values are correlated with a reduction in TSH and an increase in FT3 and FT4. There is a statistically significant increase in TPOAb in the most exposed workers. Conclusions: The trends of thyroid hormones may suggest a tendency towards hyperthyroidism for higher lead exposure, while the increase in TPOAb could indicate a greater predisposition to the development of autoimmune thyroid diseases.